2016
DOI: 10.1590/1679-78252211
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Void Effect on Shear Stress Field in Bonded Stepped-Lap Joint

Abstract: In this paper, an adhesively-bonded stepped-lap joint suffering from a void within its adhesive layer is investigated. The void separates the layer into two sections. The joint is under tensile load and materials are isotropic and assumed to behave as linear elastic. Classical elasticity theory is used to determine shear stress distribution in the separated sections of adhesive layer along the overlap length. A set of differential equations was derived and solved by using appropriate boundary conditions. Finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Both finite element analysis and the proposed model suggest various peel stresses in the TA/BA interfaces unlike, most current viscoelastic solutions that disregard the peel stress or only predict one value for both interfaces. 18–20…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both finite element analysis and the proposed model suggest various peel stresses in the TA/BA interfaces unlike, most current viscoelastic solutions that disregard the peel stress or only predict one value for both interfaces. 18–20…”
Section: Resultsmentioning
confidence: 99%
“…Both finite element analysis and the proposed model suggest various peel stresses in the TA/BA interfaces unlike, most current viscoelastic solutions that disregard the peel stress or only predict one value for both interfaces. [18][19][20] Comparison between single stepped-lap and single-lap model In this section, the stress distribution in the single stepped-lap and the single-lap adhesive joints is compared under axial load. For this purpose, the shear stress in the adhesive mid-plane and the peel stresses in the TA and BA interfaces in both models (single stepped-lap and single-lap) with similar material and dimensions are calculated using the 3PFVF model and relevant results at t = 0 are shown in Figures 11-13.…”
Section: Verification Using Finite Element Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] . Ghoddous et al [7] conducted a study on the influence of the gap in the bonding layer of the lap joint on the performance of the joint, and the study showed that the stress distribution of the stepped lap joint with the gap was better than that of the single lap joint and the double lap joint. Han et al [8] revealed the tensile failure mechanism of the stepped bond structure of composite materials by using FEM static stress analysis, experimental research, and CDM methods.…”
Section: Introductionmentioning
confidence: 99%